1998
DOI: 10.1017/s135772980000922x
|View full text |Cite
|
Sign up to set email alerts
|

Annual energy intake and the metabolic and reproductive performance of beef cows differing in body size and milk potential

Abstract: The metabolic status and reproductive performance of four pure breeds of beef cow (small size and low milk potential, Aberdeen Angus; small size and high milk potential, Welsh Black; large size and low milk potential, Charolais; and large size and high milk potential, Simmental) were monitored during their first two parities. Heifers from each breed were allocated to one of two levels of annual energy intake relative to metabolic body weight (M 075 ) (mean daily intakes equivalent to 705 and 820 kj/kg M°' 75 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also, Sinclair et al (1998) suggested that mechanisms controlling the anabolic processes governing maternal growth are antagonistic towards the mechanisms controlling reproduction. These authors found that the catabolism of lean tissue rather than fat tissue during the early post-partum period impaired reproductive performance in young cows.…”
Section: Cowsmentioning
confidence: 99%
“…Also, Sinclair et al (1998) suggested that mechanisms controlling the anabolic processes governing maternal growth are antagonistic towards the mechanisms controlling reproduction. These authors found that the catabolism of lean tissue rather than fat tissue during the early post-partum period impaired reproductive performance in young cows.…”
Section: Cowsmentioning
confidence: 99%
“…However, in the current experiment, multiparous cows displayed higher βHB only during the rst week postpartum, and no parity effect on NEFA concentrations. For Bos taurus beef cows, Sinclair et al [10] found higher βHB postpartum for primiparous than nulliparous during the rst postpartum weeks, consistent with increased βHB for primiparous at days 7 and 21. Based on the contrasting results of NEFA and βHB between studies, it seems that energy status parameters are impacted differently between parity in dairy and beef cows since they differ in milk production potential.…”
Section: Discussionmentioning
confidence: 90%
“…Increased SUN can also be related to the mobilization of amino acids for gluconeogenesis, so the deamination process is responsible for the enhanced blood urea (a by-product of protein catabolism). For young cows, Sinclair et al [10] suggested a preference for catabolism of lean tissue rather than fat tissue during the early postpartum period, although some studies did not nd a difference in SUN between parities [31,36]. Also, a likely explanation that supports these outcomes is that as multiparous cows calved with better BCS, they had more adipose tissue to support milk production, so they had to mobilize less protein to support gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the current experiment, multiparous cows displayed higher βHB only during the first week postpartum, and no parity effect on NEFA concentrations. For Bos taurus beef cows, Sinclair et al [ 10 ] found higher βHB postpartum for primiparous than nulliparous during the first postpartum weeks, consistent with increased βHB for primiparous at days 7 and 21. Based on the contrasting results of NEFA and βHB between studies, it seems that energy status parameters are impacted differently between parity in dairy and beef cows since they differ in milk production potential.…”
Section: Discussionmentioning
confidence: 92%